Konstruksi Independensi Auditor Dalam Perspektif Syariat Islam - Yuhardiansyah Yuhardiansyah; Herlina Helmy; Salma Taqwa (Universitas Negeri Padang, 2019)
This study aims to prove scientifically about (1) the perspective of Muslim auditors in interpreting auditor independence, (2) a comparison of ways to interpret independence, between Muslim auditors and non-Muslim auditors, and (3) values that weaken and values that reinforce auditor independence.The research method used is interpretive qualitative, the concept of independence is explored using Blumer's symbolic interaction approach or Chicago School of Symbolic Interactionism (CSSI). Interview methods with several Muslim and non-Muslim auditors were used to collect data. Triangulation is used to test the validity of the interview data, while coding of the data is used to simplify the process of data interpretation. The results of this study are, (1) the definition of independence based on the perspectives of Muslim and non-Muslim auditors includes attitudes and patterns of relationships, (2) Islamic values related to social values contained in Islamic Sharia’ which can weaken independence and strengthen independence.